Evaluasi Inspeksi Alat Pemadam Api Ringan Menggunakan Pendekatan Job Safety Analysis - Yusufatama Widjaya; Nina Aini Mahbubah (Fakultas Teknik, 2022)
PT XYZ is a potential and growing agro-industry enterprise in Indonesia. This company produces agricultural chemical products. The firm also implements health safety management as a standard operational procedure to create a safe and healthy workplace environment. A fire extinguisher is considered a precautionary tool in case of a fire accident in the workplace. Even though there has never been a fire accident in the workplace that required a fire extinguisher, periodic fire extinguisher inspections are required to be adequately used in an urgent situation. A critical finding during internal HSE audits was that tools performance was not following PERMENAKER 04/MEN/1980. As a result, it is necessary to evaluate the fire extinguisher inspection. This study aims to identify the potential hazards and evaluate current procedures of fire extinguisher inspection using the Job Safety Analysis approach. This study found that the primary hazard is tripping, scratching, and the fire extinguisher falls. Improved work safety can be done by carrying out seven secure steps and identifying prevention procedures for potential hazards during fire extinguiser’s inspection procedures.